2019
DOI: 10.1097/brs.0000000000002907
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year Outcomes of Cervical Disc Replacement With the BRYAN Cervical Disc

Abstract: Study Design. A prospective, randomized multicenter IDE trial between May 2002 and October 2004. Objective. The aim of this study was to report on the 10-year safety and efficacy of BRYAN cervical disc arthroplasty (CDA). Summary of Background Data. Cervical disc arthroplasty (CDA) is a potential alternative for anterior cervical decompression and fusion (ACDF) with the hope that maintenance of motion may de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(56 citation statements)
references
References 30 publications
1
55
0
Order By: Relevance
“…According to these meta-analyses, CTDR seems to be superior to ACDF with regard to most clinical parameters [14,15]. Given the short-term clinical success of CTDR around the world, criticisms in the literature regarding long-term durability of these prostheses resulted in publications of midterm results [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…According to these meta-analyses, CTDR seems to be superior to ACDF with regard to most clinical parameters [14,15]. Given the short-term clinical success of CTDR around the world, criticisms in the literature regarding long-term durability of these prostheses resulted in publications of midterm results [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…5,6,9,[11][12][13][14][15] Additionally, long-term follow-up studies have demonstrated favorable results of arthroplasty, particularly in terms of pain, disability, neurological status and patient satisfaction. [16][17][18][19][20][21][22] Moreover, past studies have also reported decreased rates of radiographic adjacent segment degeneration and symptomatic adjacent segment disease after CDA compared to ACDF. [11][12][13]17,[23][24][25][26][27] Although these studies have described encouraging results, some reports have noted limitations with generalizability, and elevated risks of selection bias due to the initial industrysponsored trials' strict inclusion and exclusion criteria.…”
Section: Introductionmentioning
confidence: 99%
“…10,28 In terms of revision and readmission rates, CDA appears to perform similarly, if not better, than ACDF. 17,[21][22][23][24]26,29,30 While some studies have demonstrated decreased rates of reoperation at the adjacent level after CDA, Kelly and colleagues noted no significant difference in secondary surgery when comparing arthroplasty to ACDF up to 5-year follow-up. [21][22][23]29 Similarly, Bhashyam et al reported no significant differences with reoperation rates between ACDF and CDA.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Randomized controlled studies (RCTs) also demonstrated that CDR could prevent adjacent segment degeneration (ASD) compared with ACDF. [5][6][7] Therefore, CDR has become an important option for the treatment of CDDD.…”
Section: Introductionmentioning
confidence: 99%